Experimental and numerical studies on combustion characteristics of N2-diluted CH4 and O2 diffusion combustion in a packed bed. Issue 9 (11th September 2019) - Li, Houping; Shi, Junrui; Mao, Mingming; Liu, Yongqi
Abstract : Experimental and numerical studies were conducted to determine the combustion characteristics of gas diffusion combustion in a porous combustor packed with 2.5 mm or 3.5 mm alumina pellets, special attention being focused on the effect of packed bed height ( h ) on combustion, NO and CO emissions. The pollutant emission of diffusion filtration combustion is studied with different packed bed lengths in the range of 40 mm ≤ h ≤ 240 mm, fixed excess air ratio of 1.88 and fixed gas inlet velocity of 0.06 m s −1 . Results show that both immersed and surface flames coexist in the combustor. Although porous media enhance the mixing and diffusion processes, the diffusion flame shape is still observed from the side and top views of the combustor, and the diffusion filtration retains properties of diffusion combustion. The immersed flame is always observed with increase in h, whereas the height of surface flame decreases. The NO emission decreases sharply when h is increased from 40 mm to 120 mm. However, the NO emission decreases slightly when h > 120 mm. In the investigated range of h, it is shown that h has a significant influence on the CO emission, an increase in h leading to a constant increase in CO for the combustors packed with 2.5 mm or 3.5 mm pellets. The maximum CO emission is 662 ppm and the minimum value is 67 ppm. In the scope of this study, the temperature on the external wall of the combustor reaches 434–513°C.